Pengembangan Bahan Ajar Menyimak Bahasa Indonesia Berbasis Kearifan Lokal Cerita Rakyat Sunan Bonang Di Sekolah Dasar - Fera; Rohmat; Mario Fahmi Syahrial; Siti Ika Nur Jannah (Paedagogie, 2026)
This study aims to develop Indonesian language listening instructional materials based on the Sunan Bonang folklore as local wisdom of Tuban Regency for third-grade students of SD Negeri Wadung, Jenu District, Tuban Regency, East Java. The study employed a Research and Development (R&D) design using the ADDIE model, encompassing five systematic stages: Analysis, Design, Development, Implementation, and Evaluation. Data were collected through classroom observation, teacher interviews, expert validation sheets for content and media, a four-aspect listening assessment rubric, and pre-test and post-test instruments administered to 24 third-grade students. Quantitative data were analyzed using validation score percentages and the Normalized Gain (N-Gain) formula, while qualitative data were derived from validator notes and recommendations. The results indicate that the instructional materials achieved a combined validation average of 91.0% (Very Valid), with content expert validation at 92.3% and media expert validation at 89.6%. The effectiveness of the materials was demonstrated by a significant increase in mean scores from 52.00 on the pre-test to 83.33 on the post-test, yielding an average N-Gain of 0.65 (moderate category), with all students (100%) achieving the minimum mastery criterion following implementation. The study concludes that Sunan Bonang folklore can be systematically transformed into valid and effective listening instructional materials through the ADDIE model, providing a replicable framework for local wisdom-based instructional material development in other regions of Indonesia.